PERKEMBANGAN BAHASA ARAB MODERN DALAM PERSPEKTIF SINTAKSIS DAN SEMANTIK PADA MAJALAH ALJAZEERA - Adit Tiawaldi; Muhbib Abdul Wahab (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
This study aimed to investigate the modern Arabic language used by Aljazeera online. It focused on the analysis of the development of meaning and language structure. The object of this research is Aljazeera online magazine in the form of lexical, grammatical and contextual meaning analysis, and syntactic research in the form of phrase, clause and verbal analysis. The theory of this research was al-Nazhariyyah al-Siyaqiyyah or contextual theory developed by J.R Firth. This research used a library research using two approaches, namely the sociolinguistic and lexicostatistic approaches. The primary source of this research was Aljazeera online magazine. This study revealed that the modern Arabic language used by Aljazeera magazine had undergone much development in meaning and structure and the development of science and technology had also a great influence on the development of its vocabulary in various fields such as politics, economy and science and technology.